2016
DOI: 10.1051/e3sconf/20160916011
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of coupled heat and moisture flows around a buried electrical cable

Abstract: Abstract. The admissible current within a buried electrical power cable is limited by the maximum allowed temperature of the cable (Joule effect). The thermal properties of the surrounding soil controls heat dissipation around the cable. The main focus of the study was to evaluate the coupled heat and moisture flow around such buried electrical cables. The heat dissipation of a buried power cable was simulated in the surrounding soil at unsteady conditions. The hydro-thermal coupling was modelled by taking int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…However, the thermal properties of a given soil depend on their moisture content (w%) and density. Some studies showed that the cable temperature increase induces a drying of the soil [6,7], that phase being followed by a progressive rehydration when the temperature of the cable decreases.…”
Section: Introductionmentioning
confidence: 99%
“…However, the thermal properties of a given soil depend on their moisture content (w%) and density. Some studies showed that the cable temperature increase induces a drying of the soil [6,7], that phase being followed by a progressive rehydration when the temperature of the cable decreases.…”
Section: Introductionmentioning
confidence: 99%